Related factors of dental caries and molar incisor hypomineralisation in a group of children with cystic fibrosis - KARGÜL, BETÜL; KARADAĞ, BÜLENT TANER; PEKER, MEHMET SERTAÇ; GÖKDEMİR, YASEMİN (Springer Verlag, 2014)
Aim: To investigate dental caries and molar incisor hypomineralisation (MIH)-related factors such as treatment, diet, brushing and salivary factors in children with cystic fibrosis (CF) compared with healthy peers. Study design: A cohort study was performed. Methods: This study was performed on 30 CF children comprising patients at the Faculty of Medicine and 30 control children recruited from the Dental School. Salivary factors, dental caries, MIH, daily diet, brushing habits were analysed. Statistical analysis was calculated by SPSS for Windows. Results: Decay missing filled teeth (DMF-T) score was 4.6 ± 4.0 in CF and 7.7 ± 2.7 in control (p = 0.001). 43 % of CF children with MIH were found to use antibiotics, but no significant difference in the caries experience was found with antibiotic usage (p > 0.05). DMF-T of CF adolescents (23 %) who use Tobramycin was 7 ± 3.5. DMF-T of CF children (20 %) who take other antibiotics was 2.5 ± 3.5, but no statistical difference was found (p = 0.054). Saliva pH, salivary flow rate, and buffering capacity were not found statistically significant (p > 0.05). Statistics: Percentage arithmetic mean value, standard deviation, independent sample t test, Fisher's exact test, Chi-square test and Mann-Whitney U test were used, while a p value of <0.05 was considered statistically significant. Conclusions: Medication and diet could be considered as a risk factor for dental caries and factors such as salivary pH, good oral hygiene could play a protective role for oral health CF children. MIH frequency and lower caries experience seen in CF children could be due to salivary factors or pharmacological treatment they take. The multidisciplinary approach team would be advantageous in the management of children with CF and oral health should be under control during early years of life by paediatric dentists. © 2014 European Academy of Paediatric Dentistry.
Keywords: Children; Cystic fibrosis; Dental caries; Molar incisor hypomineralisation; Saliva